A prototype of secure telephone communication - Lifeng Lin; Zijian Zhou; Peihe Jiang; Sanjun Liu; Lai Wei; Bingli Jiao (Scientific Reports)
Abstract This paper investigates a secure wireline telephone communication system that implements physical layer security (PLS) through artificial noise (AN) injection. The PLS-based telephone system strategically superimposes AN onto transmitted signals to prevent potential eavesdropping attempts along the twisted-pair line while enabling clean signal recovery at legitimate receivers through coordinated AN cancellation. Experimental results demonstrate its effectiveness against wiretapping, with implemented prototype circuits confirming the practical feasibility of our AN-based security approach while maintaining communication quality.